2013
DOI: 10.1007/s00421-013-2725-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adiposity on insulin action after acute and chronic resistance exercise in non-diabetic women

Abstract: Seven weeks of PRT increases insulin sensitivity and reduces glucose-stimulated insulin secretion in NBF, but not HBF women. Obesity attenuates exercise-induced improvements in glucose regulation in young non-diabetic women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…It is possible that obese subjects and/or subjects with metabolic syndrome may have a more blunted change in Si in response to resistance exercise training. Malin et al (24) recently showed that nondiabetic obese women experienced blunted improvements in postprandial Si compared with lean controls after a RT program. In another study, Layne et al (23) found that subjects with metabolic syndrome have blunted improvements in Si after RT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that obese subjects and/or subjects with metabolic syndrome may have a more blunted change in Si in response to resistance exercise training. Malin et al (24) recently showed that nondiabetic obese women experienced blunted improvements in postprandial Si compared with lean controls after a RT program. In another study, Layne et al (23) found that subjects with metabolic syndrome have blunted improvements in Si after RT.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose (50%) was injected at time zero, through an intravenous catheter placed in the antecubital space at 0.3 g/kg body mass, and insulin (0.025 U/kg body mass) was injected at minute 20. Twenty-nine blood samples (at minutes 0, 2,3,4,5,6,8,10,12,14,16,19,22,23,24,25,27,30,40,50,60,70,80,90,100,120,140,160,180) were obtained, centrifuged, and stored at Ϫ80°C. Insulin was measured by immunoassay (Access Immunoassay System, Beckman Coulter, Fullerton, CA), and glucose with an oxidation reaction (YSI 2300, Yellow Springs, OH).…”
Section: Subjects (Screening Inclusion and Exclusion Criteria)mentioning
confidence: 99%
“…T2D is characterized by elevated blood glucose levels caused by an impairment in glucose tolerance from the development of insulin resistance (IR) and relative insulin deficiency (Mann et al, 2014). However, many individuals with IR maintain normal glycaemia due to compensatory increases in pancreatic insulin secretion (Malin et al, 2013; Malin et al, 2016). Thus, the preservation of pancreatic 𝛽‐cell function in IR may be fundamental to the prevention of T2D.…”
Section: Introductionmentioning
confidence: 99%
“…With the results of glucose and insulin at time 0 min, IR will be calculated from the homeostasis model of IR (HOMA-IR) using the formula glucose (mmol) x insulin (μU/mL) ÷ 22.5 [ 67 ] and insulin sensitivity will be calculated using the quantitative insulin sensitivity check index (QUICKI) [ 68 ]. Other indexes of insulin sensitivity and IR will be calculated from the results of the OGTT [ 69 ], such as the Oral Glucose Insulin Sensitivity index [ 70 ], the Matsuda index [ 71 ], Cederholm's insulin sensitivity index [ 72 ], skeletal muscle insulin sensitivity index [ 73 , 74 ], the glucose-stimulated insulin secretion index [ 75 ], oral disposition index [ 76 , 77 ], the Gutt index [ 78 ], the Avignon et al index [ 79 ], Belfiore et al index [ 80 ], the Stumvoll et al index [ 81 ], and the McAuley et al index [ 82 ]. Furthermore, total glucose and insulin area under the curve (AUC) will be calculated using the trapezoidal method [ 83 ].…”
Section: Methodsmentioning
confidence: 99%